Pretreatment liquid, zinc-coated aluminum-magnesium photovoltaic profile, and preparation method and application thereof
By using a pretreatment liquid containing components such as aqueous resin to form a pretreatment film, the problem of insufficient adhesion of photovoltaic brackets and photovoltaic frame coatings of galvanized aluminum-magnesium steel is solved, and high adhesion and service life are extended under aging resistance conditions are achieved.
Patent Information
- Application Number
- CN202411560864.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-04-01
AI Technical Summary
The prior art is difficult to effectively improve the adhesion of the coating layer of the photovoltaic brackets and photovoltaic frames of galvanized aluminum-magnesium steel, resulting in the coating being easily shedded and affecting the service life.
A pretreatment liquid including aqueous resin, perfluoropolyether, adhesion promoter, corrosion inhibitor, curing agent and additive is used to form a pretreatment film to improve adhesion of the coating layer by using a combination of zinc-aluminum-magnesium plating layer.
It significantly improves the adhesion between the coating layer and the galvanized aluminum-magnesium steel, and can maintain excellent adhesion under aging resistance and extend the service life of photovoltaic modules.
Smart Images

Figure BDA0005117835350000021 
Figure BDA0005117835350000091 
Figure BDA0005117835350000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photovoltaic profile surface treatment, in particular to a pretreatment liquid for galvanized aluminum-magnesium photovoltaic profiles, specifically to a pretreatment liquid for improving the adhesion between a coating layer of a photovoltaic profile and a zinc-aluminum-magnesium coating, a galvanized aluminum-magnesium photovoltaic profile, and a manufacturing method and application thereof. Background Art
[0002] At present, the metal materials (except aluminum profiles) commonly used in photovoltaic modules for photovoltaic brackets and photovoltaic frames are most preferably galvanized aluminum-magnesium steel with good corrosion resistance (that is, a layer of zinc-aluminum-magnesium coating is plated on the outer surface of the steel body). Galvanized aluminum-magnesium steel is conductive. When installing electrical equipment in photovoltaic power stations, the original color galvanized aluminum-magnesium steel frames need to be insulated or sprayed with insulating protective coatings during production and use to prevent safety hazards. In addition, zinc, aluminum, magnesium, etc. are all active metals with low electrode potential and low density. They show high chemical and electrochemical activity and are prone to oxide black spots, which not only affect the overall appearance, but also make it difficult for polymer coatings to adhere. Adhesion is one of the important factors that determine the failure of the coating. Without good adhesion support, the coating will fall off on a large scale, and other properties will become meaningless, which will greatly affect the service life of the photovoltaic brackets and photovoltaic frames of the galvanized aluminum-magnesium steel system.
[0003] Therefore, in order to make the photovoltaic bracket and photovoltaic frame of the galvanized aluminum-magnesium steel system meet the requirement of 25-30 years of service life. The prior art (such as publication number CN116426153A) discloses an anti-corrosion profile, which includes a substrate and an alloy plating layer and an anti-corrosion coating arranged on the surface of the substrate from the inside to the outside, and the anti-corrosion coating includes a primer and a topcoat; by adding at least 5% (by weight percentage) of 2 to 5 layers of graphene to both the primer and the topcoat, the anti-corrosion coating has good anti-corrosion performance and improves the adhesion of the paint film.
[0004] However, the existing anti-corrosion coating of such anti-corrosion profiles has limited effect on improving adhesion, and the added graphene is also conductive, which increases safety hazards. Therefore, it is urgent to develop an environmentally friendly and safe pre-treatment liquid for improving the aging-resistant adhesion between the coating layer and the photovoltaic bracket (or photovoltaic frame) of the galvanized aluminum-magnesium steel system. Summary of the invention
[0005] The purpose of the present invention is to provide a pretreatment liquid for galvanized aluminum-magnesium photovoltaic profiles, a galvanized aluminum-magnesium photovoltaic profile, and a production method and application thereof in view of the deficiencies in the prior art.
[0006] Based on this, the present invention discloses a pretreatment solution for zinc-coated aluminum-magnesium photovoltaic profiles, which comprises the following raw materials in parts by weight:
[0007]
[0008] Wherein, the water-based resin is at least one of a water-based polyester resin, a water-based fluorocarbon resin, a water-based hydroxylated acrylic resin, and a water-based polyaspartic acid resin.
[0009] Preferably, the waterborne polyester resin has a hydroxyl value of 75-110 mgKOH / g and a viscosity of 1500-2500 mPa·s at 25°C;
[0010] The water-based fluorocarbon resin has a hydroxyl value of 50-80 mgKOH / g and a viscosity of 1500-2500 mPa·s at 25°C;
[0011] The water-based hydroxy acrylic resin has a hydroxyl value of 60-80 mgKOH / g and a viscosity of 3000-5000 mPa·s at 25° C.;
[0012] The water-based polyaspartic acid resin has a hydroxyl value of 70-100 mgKOH / g and a viscosity of 1000-2000 mPa·s at 25° C.
[0013] More preferably, the water-based polyester resin is at least one of Shurui Chemical's water-based polyester resin AP-50, Shurui Chemical's water-based polyester resin AC-8008, and Kelisen's water-based polyester resin KN2774H-7;
[0014] The water-based fluorocarbon resin is at least one of the water-based fluorocarbon resin WH-D2245 of Wanbo New Materials, the water-based fluorocarbon resin WF-FM261 of Wanbo New Materials, and the water-based fluorocarbon resin HD-8665 of Xunda New Materials;
[0015] The water-based hydroxylated acrylic resin is a water-based hydroxylated acrylic resin of Honghui New Materials 1121. Water-based hydroxyl acrylic resin of Honghui New Materials 2150, at least one of the water-based hydroxyl acrylic resin PA-4220 of Guanzhi New Materials;
[0016] The water-based polyaspartic acid resin is at least one of the water-based polyaspartic acid resin TOCPOLYNH-283W of Tuochuang Polymer New Materials, the water-based polyaspartic acid resin 1712A of Anqing Decheng Chemical, and the water-based polyaspartic acid resin N1715 of Anqing Decheng Chemical.
[0017] Further preferably, the perfluoropolyether is perfluoropolyether LF08 produced by Langrun Technology and / or perfluoropolyether HP300 produced by Dow Corning.
[0018] Further preferably, the adhesion promoter is the adhesion promoter SY-5620 of Weiner New Materials, the adhesion promoter W530 of Jintu Chemical, the adhesion promoter of Evonik Specialty Chemicals At least one of AddBond LTW;
[0019] The corrosion inhibitors are CS700 from Aolin Environmental Protection Technology, CS500 from Aolin Environmental Protection Technology, and CS500 from Dingrui New Materials. At least one of FM-CE-DR2002;
[0020] The curing agent is at least one of blocked dicyclohexylmethane diisocyanate, blocked hexamethylene diisocyanate, blocked isophorone diisocyanate and blocked diphenylmethane-4,4'-diisocyanate.
[0021] Further preferably, the auxiliary agent includes 0.1-1.0 parts of a catalyst, 0.3-1.5 parts of a leveling agent and 0.5-1.5 parts of a dispersant.
[0022] Further preferably, the catalyst is at least one of dibutyltin dilaurate, dibutyltin diacetate, dibutyltin didodecylsulfide, and stannous octoate;
[0023] The leveling agent is at least one of the leveling agent WS-707W of Wuseshi New Materials, the leveling agent SY-5066 of Weina New Materials, and the leveling agent SY-A3333 of Weina New Materials;
[0024] The dispersant is dispersant QR-100 from Dongrun Chemical and / or dispersant HP-2019 from Huihong New Materials.
[0025] The present invention also discloses a method for manufacturing a galvanized aluminum-magnesium photovoltaic profile, comprising the following manufacturing steps:
[0026] Step 1, firstly plate a zinc-aluminum-magnesium coating on the outer surface of the steel body, and then degrease the outer surface of the zinc-aluminum-magnesium coating;
[0027] Step 2, fully mix the raw materials weighed according to the pretreatment liquid formula, stir evenly, and obtain the pretreatment liquid; the pretreatment liquid is a pretreatment liquid for zinc-coated aluminum-magnesium photovoltaic profiles according to any one of claims 1 to 6;
[0028] Step 3, applying the pretreatment liquid to the outer surface of the zinc-aluminum-magnesium coating, curing to form a pretreatment film on the outer surface of the zinc-aluminum-magnesium coating, and cooling;
[0029] Step 4: Apply the coating to the outer surface of the pre-treatment film and solidify it to form a coating layer on the outer surface of the pre-treatment film to obtain a zinc-coated aluminum-magnesium photovoltaic profile.
[0030] Preferably, in step 1, the weight of the zinc-aluminum-magnesium coating is ≥150g / m 2 , thickness ≥ 20 μm; the materials used for the zinc-aluminum-magnesium coating include the following raw materials by weight percentage: aluminum 1.0-11.0%, magnesium 1.0-3.0%, silicon 0.1-1.5%, trace elements 0.1-1.5%, and the rest is zinc;
[0031] In step 2, the stirring rate is 600-1000 r / min and the time is 10-15 min;
[0032] In step 3, the pretreatment liquid is solidified at a temperature of 90-110° C. for 5-10 min to form a pretreatment film with a thickness of 0.5-2 μm;
[0033] In step 4, the coating is polyurethane coating, fluorocarbon coating, polyester coating, acrylic coating, polyaspartic acid coating or epoxy coating; the curing temperature of the coating is 100-150° C. and the curing time is 10-15 minutes to form a coating layer with a thickness of 25-50 μm.
[0034] The present invention also discloses a galvanized aluminum-magnesium photovoltaic profile, which is made by the manufacturing method of a galvanized aluminum-magnesium photovoltaic profile described above in the content of the present invention; the galvanized aluminum-magnesium photovoltaic profile comprises a steel body, and the outer surface of the steel body is sequentially covered with a zinc-aluminum-magnesium coating, a pretreatment film and a coating layer.
[0035] The present invention also discloses an application of a galvanized aluminum-magnesium photovoltaic profile, and the galvanized aluminum-magnesium photovoltaic profile is used as a photovoltaic frame and / or a photovoltaic bracket in a photovoltaic module.
[0036] Compared with the prior art, the present invention has at least the following beneficial effects:
[0037] (1) The pretreatment liquid of the present invention is prepared by the combination of 5-25 parts of aqueous resin, 5-15 parts of perfluoropolyether, 0.4-1.2 parts of adhesion promoter, 0.5-1.5 parts of corrosion inhibitor, 10-20 parts of curing agent, 0.9-4 parts of auxiliary agent and 60-80 parts of water. The pretreatment liquid can greatly improve the adhesion between the coating layer and the galvanized aluminum-magnesium steel material (i.e., the steel material body with a zinc-aluminum-magnesium coating on the outer surface) used for the photovoltaic frame (or photovoltaic bracket), especially after resistance to boiling water aging, high temperature boiling aging, constant humidity and heat aging, humidity and freezing aging and heat cycle aging. The pretreatment liquid can be compatible with various existing coatings (such as polyurethane coatings, fluorocarbon coatings, polyester coatings, acrylic coatings, polyaspartic acid coatings, etc.) used for galvanized aluminum-magnesium photovoltaic profiles, and is particularly compatible with fluorocarbon coatings, polyurethane coatings or polyester coatings used for galvanized aluminum-magnesium photovoltaic profiles.
[0038] (2) Moreover, the pretreatment liquid can effectively control the appearance abnormalities such as black spots and scratches produced during the transportation of galvanized aluminum-magnesium steel and before the protective coating layer is applied, and it is environmentally friendly, safe and reliable.
[0039] (3) The preparation process of the pretreatment solution is simple, does not require complicated synthesis, and can be used after sufficient stirring.
[0040] (4) The construction process is simple and has a high tolerance. It can be roller coated, dip coated, or sprayed on the surface of galvanized aluminum-magnesium steel.
[0041] (5) Under the premise that the type of coating and the thickness of the coating layer are the same, compared with the galvanized aluminum-magnesium photovoltaic profile without a pre-treatment film, the present invention adds a pre-treatment film between the aluminum-magnesium coating layer and the coating layer, so that the life of the galvanized aluminum-magnesium photovoltaic profile can be extended by 5-15 years, which can effectively protect the photovoltaic frame and / or photovoltaic bracket used in the photovoltaic module for a longer period of time. DETAILED DESCRIPTION
[0042] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below in conjunction with specific implementation methods.
[0043] Example 1
[0044] A pretreatment solution for zinc-aluminum-magnesium photovoltaic profiles in this embodiment includes the following raw materials in parts by weight:
[0045] Wanbo New Materials water-based fluorocarbon resin WH-D2245 is 15 parts, Langrun perfluoropolyether LF08 is 15 parts, dibutyltin dilaurate is 0.5 parts, Wuseshi New Materials leveling agent WS-707W is 0.6 parts, Dongrun Chemical dispersant QR-100 is 0.8 parts, Weina New Materials adhesion promoter SY-5620 is 0.8 parts, Aolin Environmental Protection Technology corrosion inhibitor CS700 is 0.8 parts, blocked dicyclohexylmethane diisocyanate is 14 parts, and deionized water is 70 parts.
[0046] A zinc-aluminum-magnesium-coated photovoltaic profile in this embodiment includes a steel body, and the outer surface of the steel body is sequentially coated with a zinc-aluminum-magnesium coating, a pretreatment film and a coating layer.
[0047] Among them, the weight of zinc-aluminum-magnesium coating is 275g / m 2 The thickness is 25 μm. The materials used for the zinc-aluminum-magnesium coating include the following raw materials by weight percentage: 5.5% aluminum, 2.5% magnesium, 0.95% silicon, 0.9% trace elements, and the rest is zinc.
[0048] The coating used in the coating layer is polyurethane coating, and the thickness of the coating layer is 25-35 μm (such as 30 μm).
[0049] The thickness of the pre-treatment film is 1 μm.
[0050] A method for manufacturing a galvanized aluminum-magnesium photovoltaic profile in this embodiment includes the following manufacturing steps:
[0051] Step 1: First, plate a zinc-aluminum-magnesium coating on the outer surface of the steel body, then wipe the outer surface of the zinc-aluminum-magnesium coating with alcohol to remove oil and grease, and set it aside.
[0052] Step 2: Fully mix the raw materials weighed according to the formula of the pre-treatment liquid, and stir at 800 r / min for 10 min to obtain the pre-treatment liquid for zinc-coated aluminum-magnesium photovoltaic profiles, and set aside.
[0053] Step 3: spray the pretreatment liquid on the outer surface of the zinc-aluminum-magnesium coating, cure it at 100° C. for 8 minutes to form a pretreatment film on the outer surface of the zinc-aluminum-magnesium coating, cool it, and set it aside.
[0054] Step 4: spray the polyurethane coating on the outer surface of the pretreatment film and cure it at 100° C. for 10 minutes to form a coating layer on the outer surface of the pretreatment film; thus, a galvanized aluminum-magnesium photovoltaic profile of this embodiment is obtained.
[0055] The present embodiment provides an application of a galvanized aluminum-magnesium photovoltaic profile, wherein the galvanized aluminum-magnesium photovoltaic profile is used as a photovoltaic frame and / or a photovoltaic bracket in a photovoltaic module.
[0056] Example 2
[0057] A pretreatment liquid for a galvanized aluminum-magnesium photovoltaic profile, a galvanized aluminum-magnesium photovoltaic profile, and a manufacturing method and application thereof of this embodiment refer to Example 1, and the difference between this embodiment and Example 1 is that:
[0058] In a pretreatment liquid for galvanized aluminum-magnesium photovoltaic profiles in this embodiment, the weight proportion of Wanbo New Materials water-based fluorocarbon resin WH-D2245 is changed to 20 parts, and the weight proportion of Langrun perfluoropolyether LF08 is changed to 10 parts; the remaining raw materials and their weight proportions in the pretreatment liquid of this embodiment are all referred to Example 1.
[0059] Example 3
[0060] A pretreatment liquid for a galvanized aluminum-magnesium photovoltaic profile, a galvanized aluminum-magnesium photovoltaic profile, and a manufacturing method and application thereof of this embodiment refer to Example 1, and the difference between this embodiment and Example 1 is that:
[0061] In the pretreatment solution for a galvanized aluminum-magnesium photovoltaic profile of this embodiment, the resin is replaced with: 20 parts by weight of Honghui New Material water-based hydroxy acrylic resin 1121, the weight proportion of Langrun perfluoropolyether LF08 is changed to 10 parts; the remaining raw materials and their weight proportions in the pretreatment solution of this embodiment are all referred to Example 1.
[0062] Example 4
[0063] A pretreatment liquid for a galvanized aluminum-magnesium photovoltaic profile, a galvanized aluminum-magnesium photovoltaic profile, and a manufacturing method and application thereof of this embodiment refer to Example 1, and the difference between this embodiment and Example 1 is that:
[0064] In a pretreatment liquid for galvanized aluminum-magnesium photovoltaic profiles of this embodiment, the resin is replaced by: 20 parts by weight of Shurui Chemical water-based polyester resin AC-8008, and the weight of Langrun perfluoropolyether LF08 is changed to 10 parts; the remaining raw materials and their weight parts in the pretreatment liquid of this embodiment are all referred to Example 1.
[0065] Example 5
[0066] A pretreatment liquid for a galvanized aluminum-magnesium photovoltaic profile, a galvanized aluminum-magnesium photovoltaic profile, and a manufacturing method and application thereof of this embodiment refer to Example 1, and the difference between this embodiment and Example 1 is that:
[0067] In a pretreatment liquid for galvanized aluminum-magnesium photovoltaic profiles in this embodiment, the resin is replaced by: 20 parts by weight of Tochuang Polymer New Material Water-based Aspartic Acid Resin TOCPOLY NH-283W, and the weight of Langrun Perfluoropolyether LF08 is changed to 10 parts; the remaining raw materials and their weight parts in the pretreatment liquid of this embodiment are all referred to Example 1.
[0068] Example 6
[0069] A pretreatment liquid for a galvanized aluminum-magnesium photovoltaic profile, a galvanized aluminum-magnesium photovoltaic profile, and a manufacturing method and application thereof of this embodiment refer to Example 4, and the difference between this embodiment and Example 4 is that:
[0070] In a pretreatment liquid for galvanized aluminum-magnesium photovoltaic profiles in this embodiment, the leveling agent and dispersant are replaced by: 0.6 parts of Weina New Material leveling agent SY-5066 and 0.8 parts of Huihong New Material dispersant HP-2019 respectively; the remaining raw materials and their weight portions in the pretreatment liquid of this embodiment are all referred to Example 4.
[0071] Example 7
[0072] A pretreatment liquid for a galvanized aluminum-magnesium photovoltaic profile, a galvanized aluminum-magnesium photovoltaic profile, and a manufacturing method and application thereof of this embodiment refer to Example 4, and the difference between this embodiment and Example 4 is that:
[0073] In a pretreatment liquid for galvanized aluminum-magnesium photovoltaic profiles in this embodiment, the leveling agent, dispersant and curing agent are replaced by: 0.6 parts of Weina New Material leveling agent SY-5066, 0.8 parts of Huihong New Material dispersant HP-2019, and 13 parts of blocked diphenylmethane-4,4'-diisocyanate; the remaining raw materials and their weight portions in the pretreatment liquid of this embodiment are all referred to Example 4.
[0074] Example 8
[0075] A pretreatment liquid for a galvanized aluminum-magnesium photovoltaic profile, a galvanized aluminum-magnesium photovoltaic profile, and a manufacturing method and application thereof of this embodiment refer to Example 1, and the difference between this embodiment and Example 1 is that:
[0076] In a galvanized aluminum-magnesium photovoltaic profile of the present embodiment, the coating used in its coating layer is changed to fluorocarbon coating.
[0077] In the method for manufacturing a galvanized aluminum-magnesium photovoltaic profile of the present embodiment, step 4 is changed to: spraying a fluorocarbon coating on the outer surface of the pretreatment film, and curing at 150° C. for 10 minutes to form a coating layer on the outer surface of the pretreatment film.
[0078] Example 9
[0079] A pretreatment liquid for a galvanized aluminum-magnesium photovoltaic profile, a galvanized aluminum-magnesium photovoltaic profile, and a manufacturing method and application thereof of this embodiment refer to Example 1, and the difference between this embodiment and Example 1 is that:
[0080] In a galvanized aluminum-magnesium photovoltaic profile of the present embodiment, the coating used in its coating layer is changed to polyester coating.
[0081] In the method for manufacturing a galvanized aluminum-magnesium photovoltaic profile of the present embodiment, step 4 is changed to: spraying the polyester coating on the outer surface of the pretreatment film and curing it at 120° C. for 10 minutes to form a coating layer on the outer surface of the pretreatment film.
[0082] Comparative Example 1
[0083] A galvanized aluminum-magnesium photovoltaic profile and its manufacturing method and application in this comparative example refer to Example 1, and the difference between it and Example 1 is that:
[0084] In a galvanized aluminum-magnesium photovoltaic profile of this comparative example, the pre-treatment film of Example 1 is omitted.
[0085] In the method for preparing a galvanized aluminum-magnesium photovoltaic profile in the present comparative example, steps 2-3 of Example 1 are omitted, and a polyurethane coating layer is directly prepared on the outer surface of the zinc-aluminum-magnesium coating after degreasing in step 1; thus, a galvanized aluminum-magnesium photovoltaic profile in the present comparative example is obtained.
[0086] Comparative Example 2
[0087] A pretreatment liquid, a galvanized aluminum-magnesium photovoltaic profile, and a manufacturing method and application thereof in this comparative example are described with reference to Example 2, and the difference between the comparative example and Example 2 is that:
[0088] In a pretreatment liquid of this comparative example, the weight portion of Wanbo New Materials water-based fluorocarbon resin WH-D2245 is increased to 40 parts, and the weight portion of blocked dicyclohexylmethane diisocyanate is increased to 19.5 parts correspondingly; the remaining raw materials and their weight portions in the pretreatment liquid of this comparative example are all referred to Example 2.
[0089] Comparative Example 3
[0090] A pretreatment liquid, a galvanized aluminum-magnesium photovoltaic profile, and a manufacturing method and application thereof in this comparative example are described with reference to Example 2, and the difference between the comparative example and Example 2 is that:
[0091] In a pretreatment liquid of this comparative example, the weight portion of Langrun perfluoropolyether LF08 is increased to 25 parts, and the weight portion of blocked dicyclohexylmethane diisocyanate is increased to 15 parts correspondingly; the remaining raw materials and their weight portions in the pretreatment liquid of this comparative example are all referred to Example 2.
[0092] Comparative Example 4
[0093] A pretreatment liquid, a galvanized aluminum-magnesium photovoltaic profile, and a manufacturing method and application thereof in this comparative example refer to Example 3, and the difference between the comparative example and Example 3 is that:
[0094] In a pretreatment liquid of this comparative example, 0.8 parts of Aolin Environmental Protection Technology Corrosion Inhibitor CS700 of Example 3 were omitted; the remaining raw materials and their weight proportions in the pretreatment liquid of this comparative example were all referred to Example 3.
[0095] Comparative Example 5
[0096] A pretreatment liquid, a galvanized aluminum-magnesium photovoltaic profile, and a manufacturing method and application thereof in this comparative example are described with reference to Example 4, and the difference between the comparative example and Example 4 is that:
[0097] In a pretreatment liquid of this comparative example, the weight portion of Weina New Material Adhesion Accelerator SY-5620 is increased to 3.0 parts; the remaining raw materials and their weight portions in the pretreatment liquid of this comparative example are all referred to Example 4.
[0098] Comparative Example 6
[0099] A pretreatment liquid, a galvanized aluminum-magnesium photovoltaic profile, and a manufacturing method and application thereof in this comparative example are described with reference to Example 5, and the difference between the comparative example and Example 5 is that:
[0100] In a pretreatment liquid of this comparative example, 0.8 parts of Weina New Material Adhesion Accelerator SY-5620 in Example 5 was omitted; the remaining raw materials and their weight parts in the pretreatment liquid of this comparative example were all referred to Example 5.
[0101] Comparative Example 7
[0102] A pretreatment liquid, a galvanized aluminum-magnesium photovoltaic profile, and a manufacturing method and application thereof in this comparative example are described with reference to Example 6, and the difference between the comparative example and Example 6 is that:
[0103] In a pretreatment liquid of this comparative example, the weight proportion of blocked dicyclohexylmethane diisocyanate (curing agent) is increased to 25 parts; the remaining raw materials and their weight proportions in the pretreatment liquid of this comparative example are all referred to Example 6.
[0104] Comparative Example 8
[0105] A pretreatment liquid, a galvanized aluminum-magnesium photovoltaic profile, and a manufacturing method and application thereof in this comparative example are described with reference to Example 1, and the difference between the pretreatment liquid and Example 1 is that:
[0106] In the method for making a galvanized aluminum-magnesium photovoltaic profile of the present comparative example, after the polyurethane coating is sprayed on the outer surface of the pretreatment film in step 4, the curing temperature is reduced to 50° C., and the other process parameters remain unchanged.
[0107] Performance Testing
[0108] The galvanized aluminum-magnesium photovoltaic profiles of Examples 1 to 9 and Comparative Examples 1 to 8 were subjected to a hundred-grid adhesion test after the tests of resistance to boiling water aging (SZ), resistance to high temperature cooking aging (PCT), resistance to constant humidity and heat aging (DH), resistance to humidity and freezing aging (HF) and resistance to heat cycle aging (TC), and the test results are shown in Table 1. The tests of SZ, PCT, DH, HF and TC were carried out in accordance with the standards GB / T1748-2016, JESD22-A102-C, GB / T2423.3-2016 and GB / T2423.34-2012, respectively.
[0109] Table 1
[0110]
[0111]
[0112] Combined with Table 1, we can see that:
[0113] (1) The preparation of the pretreatment liquid of Examples 1-9 is simple, without the need for complicated synthesis steps, and it can be used after sufficient stirring; the construction process is simple; the pretreatment liquid can also be adapted to various existing coatings used for zinc-aluminum-magnesium photovoltaic profiles (such as polyurethane coatings, fluorocarbon coatings, polyester coatings, acrylic coatings, polyaspartic acid coatings, etc.), which greatly improves the adhesion between the coating layer and the steel body with a zinc-aluminum-magnesium coating on the outer surface, especially after resistance to boiling water aging, high temperature cooking aging, constant humidity and heat aging, humidity and freezing aging, and heat cycle aging. It still has extremely excellent adhesion.
[0114] (2) If the pretreatment liquid is not sprayed first, but the polyurethane coating layer is directly prepared on the outer surface of the zinc-aluminum-magnesium coating (such as comparative example 1); or the raw material formula of the pretreatment liquid has one of the following situations: the resin content is too high (such as comparative example 2), the perfluoropolyether content is too high (such as comparative example 3), the corrosion inhibitor is not added (such as comparative example 4), the adhesion promoter content is too high (such as comparative example 5), the adhesion promoter is not added (such as comparative example 6), the curing agent content is too high (such as comparative example 7); or the curing temperature of the coating layer is not enough (such as comparative example 8); these will have different degrees of negative effects on the adhesion between the coating layer and the steel body with zinc-aluminum-magnesium coating on the outer surface after boiling water aging, high temperature cooking aging, constant humidity and heat aging, humidity and freezing aging and heat cycle aging, which is not conducive to extending the service life of the zinc-aluminum-magnesium photovoltaic profile in long-term harsh outdoor environment. For example, under the premise that the type of coating and the thickness of the coating layer are the same, compared with Comparative Example 1 (no pretreatment film is prepared before preparing the polyurethane coating layer), the service life of the galvanized aluminum-magnesium photovoltaic profile prepared in Example 1 can be extended by 5-15 years, and can effectively protect the photovoltaic frames and / or photovoltaic brackets used in photovoltaic modules for a longer period of time.
[0115] Among them, Weina New Materials adhesion promoter SY-5620 (a silicone-type adhesion promoter) can react with curing agents (such as blocked dicyclohexylmethane diisocyanate) to change the cyanide-hydroxyl ratio of the entire pretreatment liquid formula system, resulting in an imbalance in the formula system; therefore, if the content of the adhesion promoter is too high, the silicone in the adhesion promoter will self-polymerize after consuming the NCO in the curing agent, causing the pretreatment film to become hard and brittle, resulting in poor aging resistance and adhesion.
[0116] In addition, if the content of resin (such as Wanbo New Materials water-based fluorocarbon resin WH-D2245) in the raw material formula of the pretreatment liquid is too low, the active groups or effective ingredients participating in the curing and cross-linking reaction in the formula system of the pretreatment liquid will be too few, the cross-linking degree will become low, and the aging resistance and adhesion will also decrease.
[0117] The main functions of perfluoropolyether in the raw material formula of the pretreatment liquid are as follows: to make the galvanized aluminum-magnesium steel (i.e. the steel body with a zinc-aluminum-magnesium coating on the outer surface) have appropriate lubrication properties to ensure that the pretreatment film is not destroyed during the processing of the galvanized aluminum-magnesium steel; if the content of perfluoropolyether in the raw material formula of the pretreatment liquid is too little or absent, it will be unfavorable for the processing of galvanized aluminum-magnesium steel, and the pretreatment film is easily destroyed during the cold bending of the coiled steel, making it difficult to prepare qualified galvanized aluminum-magnesium photovoltaic profiles.
[0118] Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the embodiments of the present invention.
[0119] The technical solution provided by the present invention is introduced in detail above. Specific examples are used in this article to illustrate the principle and implementation mode of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation mode and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A pretreatment solution for zinc-coated aluminum-magnesium photovoltaic profiles, characterized in that: It includes the following raw materials in parts by weight: Wherein, the water-based resin is at least one of a water-based polyester resin, a water-based fluorocarbon resin, a water-based hydroxylated acrylic resin, and a water-based polyaspartic acid resin.
2. A pretreatment solution for zinc-coated aluminum-magnesium photovoltaic profiles according to claim 1, characterized in that: The water-based polyester resin has a hydroxyl value of 75-110 mgKOH / g and a viscosity of 1500-2500 mPa·s at 25° C.; The water-based fluorocarbon resin has a hydroxyl value of 50-80 mgKOH / g and a viscosity of 1500-2500 mPa·s at 25°C; The water-based hydroxy acrylic resin has a hydroxyl value of 60-80 mgKOH / g and a viscosity of 3000-5000 mPa·s at 25° C.; The water-based polyaspartic acid resin has a hydroxyl value of 70-100 mgKOH / g and a viscosity of 1000-2000 mPa·s at 25° C.
3. A pretreatment liquid for zinc-coated aluminum-magnesium photovoltaic profile according to claim 1 or 2, characterized in that: The water-based polyester resin is at least one of Shurui Chemical's water-based polyester resin AP-50, Shurui Chemical's water-based polyester resin AC-8008, and Kelisen's water-based polyester resin KN2774H-7; The water-based fluorocarbon resin is at least one of the water-based fluorocarbon resin WH-D2245 of Wanbo New Materials, the water-based fluorocarbon resin WF-FM261 of Wanbo New Materials, and the water-based fluorocarbon resin HD-8665 of Xunda New Materials; The water-based hydroxylated acrylic resin is a water-based hydroxylated acrylic resin of Honghui New Materials Waterborne hydroxyl acrylic resin from Honghui New Materials At least one of the water-based hydroxyl acrylic resin PA-4220 of Guanzhi New Materials; The water-based polyaspartic acid resin is at least one of the water-based polyaspartic acid resin TOCPOLY NH-283W of Tuochuang Polymer New Materials, the water-based polyaspartic acid resin 1712A of Anqing Decheng Chemical, and the water-based polyaspartic acid resin N1715 of Anqing Decheng Chemical.
4. A pretreatment liquid for zinc-coated aluminum-magnesium photovoltaic profile according to claim 1 or 2, characterized in that: The perfluoropolyether is perfluoropolyether LF08 produced by Langrun Technology and / or perfluoropolyether HP300 produced by Dow Corning.
5. A pretreatment liquid for zinc-coated aluminum-magnesium photovoltaic profile according to claim 1 or 2, characterized in that: The adhesion promoter is the adhesion promoter SY-5620 of Weiner New Materials, the adhesion promoter W530 of Jintu Chemical, and the adhesion promoter of Evonik Specialty Chemicals. At least one of AddBond LTW; The corrosion inhibitors are CS700 from Aolin Environmental Protection Technology, CS500 from Aolin Environmental Protection Technology, and CS500 from Dingrui New Materials. At least one of FM-CE-DR2002; The curing agent is at least one of blocked dicyclohexylmethane diisocyanate, blocked hexamethylene diisocyanate, blocked isophorone diisocyanate and blocked diphenylmethane-4,4'-diisocyanate.
6. A pretreatment solution for zinc-coated aluminum-magnesium photovoltaic profile according to claim 1 or 2, characterized in that: The auxiliary agent includes 0.1-1.0 parts of catalyst, 0.3-1.5 parts of leveling agent and 0.5-1.5 parts of dispersant; The catalyst is at least one of dibutyltin dilaurate, dibutyltin diacetate, dibutyltin didodecylsulfide, and stannous octoate; The leveling agent is at least one of the leveling agent WS-707W of Wuseshi New Materials, the leveling agent SY-5066 of Weina New Materials, and the leveling agent SY-A3333 of Weina New Materials; The dispersant is dispersant QR-100 from Dongrun Chemical and / or dispersant HP-2019 from Huihong New Materials.
7. A method for manufacturing a galvanized aluminum-magnesium photovoltaic profile, characterized in that: The production steps include: Step 1, firstly plate a zinc-aluminum-magnesium coating on the outer surface of the steel body, and then degrease the outer surface of the zinc-aluminum-magnesium coating; Step 2, fully mix the raw materials weighed according to the pretreatment liquid formula, stir evenly, and obtain the pretreatment liquid; the pretreatment liquid is a pretreatment liquid for zinc-coated aluminum-magnesium photovoltaic profiles according to any one of claims 1 to 6; Step 3, applying the pretreatment liquid to the outer surface of the zinc-aluminum-magnesium coating, curing to form a pretreatment film on the outer surface of the zinc-aluminum-magnesium coating, and cooling; Step 4: Apply the coating to the outer surface of the pre-treatment film and solidify it to form a coating layer on the outer surface of the pre-treatment film to obtain a zinc-coated aluminum-magnesium photovoltaic profile.
8. The method for manufacturing a galvanized aluminum-magnesium photovoltaic profile according to claim 7, characterized in that: In step 1, the weight of the zinc-aluminum-magnesium coating is ≥ 150 g / m 2 , thickness ≥ 20 μm; the materials used for the zinc-aluminum-magnesium coating include the following raw materials by weight percentage: aluminum 1.0-11.0%, magnesium 1.0-3.0%, silicon 0.1-1.5%, trace elements 0.1-1.5%, and the rest is zinc; In step 2, the stirring rate is 600-1000 r / min and the time is 10-15 min; In step 3, the pretreatment liquid is solidified at a temperature of 90-110° C. for 5-10 min to form a pretreatment film with a thickness of 0.5-2 μm; In step 4, the coating is polyurethane coating, fluorocarbon coating, polyester coating, acrylic coating, polyaspartic acid coating or epoxy coating; the curing temperature of the coating is 100-150° C. and the curing time is 10-15 minutes to form a coating layer with a thickness of 25-50 μm.
9. A galvanized aluminum-magnesium photovoltaic profile, characterized in that: The galvanized aluminum-magnesium photovoltaic profile is prepared by the method for preparing the galvanized aluminum-magnesium photovoltaic profile described in claim 7 or 8.
10. The use of a galvanized aluminum-magnesium photovoltaic profile according to claim 9, characterized in that: The galvanized aluminum-magnesium photovoltaic profile is used as a photovoltaic frame and / or a photovoltaic bracket in a photovoltaic module.
Citation Information
Patent Citations
Anti-corrosion profile, frame, solar cell module, support and photovoltaic system
CN116426153A
Cited By
Photovoltaic metal profile and preparation method and application thereof
CN121825386A